Stability and bifurcation analysis on a delayed epidemic model with information-dependent vaccination. (5th September 2019) - Zhu, Linhe; Zhou, Xiao; Li, Yimin; Zhu, Yuxun
Abstract: The propagation of vaccine information plays an important role in the spread of infectious diseases. Scholars have researched in-depth the spread of infectious diseases or focused on the differential model that only considers the characteristics of infectious diseases themselves. Little attempt has been given on the dynamic analysis of infectious diseases based on the vaccination rate depending on information. This paper primarily explores a delayed epidemic model with information-dependent vaccination, which addresses increasing the concept of propagation delay on the basis of the model in Alberto et al (2007 Theor. Population Biol. 71 301–17). Theoretical analysis reveals the local stability and Hopf bifurcation, the global stability and the optimal control of our epidemic model. Finally, numerical simulations verify the theoretical results and analyze the influence of time delay on the transmission characteristics of our model.